Code-Mixing and Code-Switching in Efl Teaching: The Implementation and Perception - Yepi Sedya Purwananti; SHELFIYA DWI NANDIYA (LINGUISTICA, 2025)
Code-mixing and code-switching have become common phenomena in this multilingual era. In Indonesia, this refers to the use of English and Indonesian. This needs to be investigated regarding how the implementation of it especially in the education sector and how students perceive it. This research focused on Mathematics Education Department students whose background was non-English students, thus it can bring new understanding related to the use of code-mixing and code-switching on other departments which closely related to English itself. This research used descriptive qualitative to analyze the implementation and students’ perception of code-mixing and code-switching. Observations and interviews were conducted to obtain data. Therefore, it was found that code-mixing and code-switching were implemented during English teaching and learning process, especially when the lecturer explaining material, giving information, and interacting with students. Hence, even though the students lack of English mastery, they were able to understand the material, information, and instructions conveyed by the lecturer.